PELATIHAN PEMANFAATAN VLOG SEBAGAI MEDIA PEMBELAJARAN MENULIS DESCRIPTIVE TEXT DI SMPN 5 SRAGI KABUPATEN PEKALONGAN - Ulya, Inayatul; Panuntun, Ida Ayu (LPPM Universitas Widya Dharma Klaten, 2023)
Learning in endemic era is not inseparable from the use of technology to support teaching and learning process. The use of technology can be realized in the use of Vlog as a learning medium. Therefore, a workshop was needed for English teachers and the students in utilizing technology in the teaching learning process. This activity was aimed to: 1) facilitating workshop to the teachers on the use of vlog as teaching medium of descriptive text, and 2) providing training to the students in writing descriptive text based on the vlog they watched. The participants of this agenda were 33 people consisting of English teachers and seventh graders of SMPN 5 Sragi, Pekalongan regency. This activity was held in some stages, they were Vlog playback, presentation, writing practice, and feedback. The result of this workshop showed that the teachers got new experiences to innovate the teaching learning process, especially the use of learning media. Meanwhile, for the students, they felt enjoyable learning atmosphere. They could develop ideas for writing descriptive text assisted by learning media in the form of “Wonderful Black Canyon” Vlog.